Manajemen Sumber Daya Manusia Berkelanjutan dan Dampaknya terhadap Kinerja Organisasi di Sektor Pariwisata Kerinci - Emelinda Emelinda; Mhd. Ikhsan (Jurnal Bisnis Kreatif dan Inovatif, 2024)
This study aims to analyze the impact of the implementation of sustainable human resource management (HR) on organizational performance in the Kerinci tourism sector. The research method used is qualitative with a case study approach, where data is collected through in-depth interviews with HR managers, employees, and company leaders in the tourism sector, as well as direct observation in the field. The results of the study show that organizations that implement sustainable HR management experience increased employee productivity, workforce welfare, and business competitiveness. Training programs related to sustainable skills and employee involvement in corporate social responsibility (CSR) initiatives play an important role in increasing employee motivation and commitment. In addition, organizations that focus on work-life balance tend to have higher levels of employee loyalty and reduced turnover. However, the study also found that small and medium enterprises (SMEs) in the Kerinci tourism sector still face challenges in implementing sustainable human resource management, mainly due to limited resources and lack of understanding of the concept of sustainability. This research recommends the need for collaboration between the government, companies, and local communities to promote sustainable HR management more broadly in Kerinci.